The relation between parental substance abuse and the attitude towards violence of the child and the mediating role of self-control and parental involvement: a cross-national multilevel analysis - Veen, Jasmijn van der (European journal of criminology, 2025)
The current study examined the relation between parental substance abuse and the child's attitude towards violence, and whether this relationship is mediated by parental involvement and the child's self-control. The study used self-report data from the Second International Self-Reported Delinquency Study, a large international study that included data from schools in 30 countries and covered topics related to delinquency and victimization of 12- to 15-year-old students (N = 68,507). With the use of a multilevel analysis, the results of this study show that there is a significant positive relationship between parental substance abuse and the child's attitude towards violence. Furthermore, the findings suggest that parental involvement and the child's self-control both mediate this relationship. Additionally, we found a significant indirect contextual effect for the self-control mediation, indicating that the mediational path gets stronger in countries with a higher prevalence of parental substance.